Кантовский проект конституционализации международного права. Есть ли у него будущее? - Хабермас, Ю. (Інститут держави і права ім. В.М. Корецького НАН України, 2007)
Вступна доповідь на ХХII Всесвітньому конгресі з філософії права і соціальної філософії «Право і справедливість в глобальному суспільстві», в якій автор (1) пояснює кантіанський проект «космополітичного правопорядку»; (2) оцінює перспективи для модифікованого космополітизму в світлі історії міжнародного права і (3) обґрунтовує переваги проекту конституціоналізації міжнародного права порівнянно з конкуруючими проектами домінування грубої сили над правом і моралізації міжнародної політики, що визначається етосом супердержави. Переклад російською мовою, з дозволу автора, професора С. І. Максимова. The opening lecture at the XXII World Congress of Philosophy of Law and Social Philosophy «Law and Justice in Global Society», in which the author (1) explains the Kantian project of ‘cosmopolitan condition’, (2) briefly verifies prospects of a modified cosmopolitism in the light of the history of international law and (3) provides the views for priority of the project of constitualisation of international law in comparison to the presently competing projects of the primacy of brute power over law and the moralisation of international politics which is determined by the ethos of superpower. (Translated into Russian, with the author’s permission, by Professor Serhiy Maksymov (Sergei Maksimov)).